2017
DOI: 10.3389/fphys.2017.00939
|View full text |Cite
|
Sign up to set email alerts
|

Human Cardiac 31P-MR Spectroscopy at 3 Tesla Cannot Detect Failing Myocardial Energy Homeostasis during Exercise

Abstract: Phosphorus-31 magnetic resonance spectroscopy (31P-MRS) is a unique non-invasive imaging modality for probing in vivo high-energy phosphate metabolism in the human heart. We investigated whether current 31P-MRS methodology would allow for clinical applications to detect exercise-induced changes in (patho-)physiological myocardial energy metabolism. Hereto, measurement variability and repeatability of three commonly used localized 31P-MRS methods [3D image-selected in vivo spectroscopy (ISIS) and 1D ISIS with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 61 publications
7
36
0
Order By: Relevance
“…The spectral quality in iRE‐MRS experiments was comparable to the gold‐standard PRESS experiments within the targeted BWs. Multiplets corresponding to 2 CH 2 , 3 CH 2 , and 4 CH 2 GABA resonances (Figure C) as well as NAA's prominent methyl singlet (Figure D) were well‐reproduced using iRE‐MRS. Phase differences between PRESS and iRE spectra, attributed to the different J‐evolution in each sequence, were noted for these multiplets.…”
Section: Resultsmentioning
confidence: 87%
“…The spectral quality in iRE‐MRS experiments was comparable to the gold‐standard PRESS experiments within the targeted BWs. Multiplets corresponding to 2 CH 2 , 3 CH 2 , and 4 CH 2 GABA resonances (Figure C) as well as NAA's prominent methyl singlet (Figure D) were well‐reproduced using iRE‐MRS. Phase differences between PRESS and iRE spectra, attributed to the different J‐evolution in each sequence, were noted for these multiplets.…”
Section: Resultsmentioning
confidence: 87%
“…Bakermans et al tested the reproducibility of a 7 min sequence in the human heart at 3 T, performing spatial localization with 3D ISIS or a combination of 1D ISIS and 1D CSI either perpendicular or parallel to the surface coil . 3D ISIS was found to be the most reproducible of these methods, giving a PCr/ATP of 1.57 ± 0.17 (mean ± SD) and a CR of 0.64.…”
Section: Discussionmentioning
confidence: 99%
“…There is some debate in the literature about the possible magnitude of changes in PCr/ATP. Bakermans et al suggested by simulations that the changes in PCr/ATP in healthy subjects upon exercise are on the order of 10%, which they concluded would be impossible to detect by 31 P‐MRS at 3 T . Exercise‐induced changes in patients with disease are known to be more substantial, perhaps because their hearts have only a limited energetic reserve because of having to compensate for disease at rest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac PCr/ATP ratios have also been found to be reduced during catecholamine stress or exercise in people with obesity and insulin resistance, although another study failed to confirm this latter observation . Whether a lower myocardial PCr/ATP ratio in diabetic cardiomyopathy is a cause or effect of the progression to heart failure is currently unknown …”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%